The Arverni and Roman wine : Roman amphorae from Late Iron Age sites in the Auvergne (Central France) : chronology, fabrics and stamps - Loughton, Matthew (Archaeopress Roman archaeology, 2014)
Large numbers of Greco-Italic and Dressel 1 amphorae were exported to many parts of Gaul during the late Iron Age and they provide a major source of information on the development and growth of the Roman economy during the late Republican period. This volume examines in detail this trade to the Auvergne region of central France and provides a typological and chronological study of the main assemblages of Republican amphorae found on the farms, agglomerations, oppida, and funerary sites, dating from the second century BC until the early first century AD. Other topics examined include the provenance of the amphorae, the stamps, painted inscriptions and graffiti, the distribution of Republican amphorae in the Auvergne, and the evidence for their modification and reuse. Finally, a gazetteer of Republican amphora findspots from France is also provided.